CTX-M-type Extended-Spectrum β-Lactamases Producing Enterobacteriaceae Isolated from Urine in a Tertiary Care Hospital, Kathmandu, Nepal - Acharya, Mahesh; Joshi, Prabhu R.; Thapa, Kamal; Paudel, Saroj; Poudel, Prativa; Bonnet, Richard (Anti-Infective Agents, 2022)
Background: Despite the global increase of CTX-M type Extended-Spectrum-β-Lactamases (ESBLs) in recent years among Enterobacteriaceae isolates from urinary tract infections, little data is available from Nepal. Objective: This study was conducted to detect the genes encoding extended-spectrum β-lactamases among Enterobacteriaceae isolated from the urine samples from Nepal. Methods: A total of 148 Enterobacteriaceae isolates were obtained from urine samples in Annapurna Neurological Institute and Allied Sciences from July 2016 to June 2017. ESBL production was detected according to the Clinical and Laboratory Standards Institute (CLSI) recommended method. PCR and sequencing were used for the detection of ESBL genes. Results: Overall, 24.3% (36/148) of the study isolates were positive for ESBL production. E. coli was the predominant ESBL-producing organism (28.8%). ESBL-producing organisms showed a high rate of resistance to ceftazidime (58.4%), cefepime (91.7%), aztreonam (83.4%), and ciprofloxacin (80.6%). Also, 30.6% of ESBL-producing organisms were multi-drug resistant. All ESBL producers were CTX-M positive; other ESBL genes were not detected. The majority of the ESBL positive organisms produced CTX-M-15 (n= 31) and few organisms (n= 5) were CTX-M-27 producers. Conclusion: The present study shows that the predominant CTX-M type ESBL in our hospital setting is CTX-M-15.
Keywords: CTX-M